Persistence of two coronaviruses and efficacy of steam vapor disinfection on two types of carpet - Jinge Huang; Angela Fraser; Xiuping Jiang (Virology Journal, 2024)
Abstract Background Coronaviruses, a group of highly transmissible and potentially pathogenic viruses, can be transmitted indirectly to humans via fomites. To date, no study has investigated their persistence on carpet fibers. Establishing persistence is essential before testing the efficacy of a disinfectant. Methods The persistence of BCoV and HCoV OC43 on polyethylene terephthalate (PET) and nylon carpet was first determined using infectivity and RT-qPCR assays. Then, the disinfectant efficacy of steam vapor was evaluated against both coronaviruses on nylon carpet. Results Immediately after inoculation of carpet coupons, 32.50% of BCoV and 3.87% of HCoV OC43 were recovered from PET carpet, compared to 34.86% of BCoV and 24.37% of HCoV OC43 recovered from nylon carpet. After incubation at room temperature for 1 h, BCoV and HCoV OC43 showed a 3.6 and > 2.8 log10 TCID50 reduction on PET carpet, and a 0.6 and 1.8 log10 TCID50 reduction on nylon carpet. Based on first-order decay kinetics, the whole gRNA of BCoV and HCoV OC43 were stable with k values of 1.19 and 0.67 h− 1 on PET carpet and 0.86 and 0.27 h− 1 on nylon carpet, respectively. A 15-s steam vapor treatment achieved a > 3.0 log10 TCID50 reduction of BCoV and > 3.2 log10 TCID50 reduction of HCoV OC43 on nylon carpet. Conclusion BCoV was more resistant to desiccation on both carpet types than HCoV OC43. Both viruses lost infectivity quicker on PET carpet than on nylon carpet. Steam vapor inactivated both coronaviruses on nylon carpet within 15 s.